PERDAGANGAN PAKAIAN BEKAS YANG DIIMPOR DALAM PERSPEKTIF HUKUM PIDANA - Annida Fadilla Fikri (JOURNAL OF LAW AND NATION, 2023)
The prohibition of importing second-hand clothing is stipulated in several Indonesian laws and regulations. However, the imposition of a 35% import duty on used clothing in Minister of Finance Regulation No. 26/PMK.010/2022 on the Classification System of Goods and the Imposition of Import Duty Tariffs on Imported Goods creates normative conflicts. This analysis advocates for the application of lex specialis derogat legi generalis to resolve normative conflicts between Minister of Trade Regulation No. 18 of 2021 on Prohibited Export and Import Goods and Minister of Finance Regulation No. 26/PMK.010/2022. In this context, Minister of Trade Regulation No. 18 of 2021 serves as lex specialis, derived from the Trade Law as its lex generalis. As the ban on importing used clothing is not explicitly repealed in both regulations, Minister of Trade Regulation No. 18 of 2021 is deemed effective. Consequently, the regulations regarding used clothing in Minister of Finance Regulation No. 26/PMK.010/2022 will be overridden, automatically prohibiting the import of second-hand clothing in Indonesia. In the process from importing used clothing to reaching consumers, various stakeholders, including the Directorate General of Customs and Excise, freight carriers, Customs Clearance Service Business Actors (PPJK), importers, businesses, and consumers, are involved. Despite imported second- hand clothing often being the result of smuggling, not all parties can be criminally held accountable. However, accountability requirements include committing a criminal act, being capable of responsibility, demonstrating culpability, and having no justifiable reasons for pardon